Biological activities and oil properties of Origanum glandulosum Desf: a review - Mechergui, Kaouther (2016)
Origanum glandulosum Desf. (Species endemic of North Africa: Tunisia and Algeria) is important medicinally as it has antimicrobial, antifungal, antioxidant, antibacterial, antithrombin, antimutagenic, angiogenic, antiparasetic and antihyperglycaemic activities. Phytochemical investigations of the species of this genus have resulted in the extraction of a number of important bioactive compounds. This emphasizes on the need of extensive study for reporting the additional information on the medicinal importance, the biological activities and properties of oil of other unattended species of Origanum glandulosum. © 2015 Springer-Verlag France.